Among Students' Internal Factors, Should Motivation be Used as One of Recruitmen for Admission of Medical Students in Indonesia? - Hikmawati Nurrokhmanti; Mora Claramita; Prattama Santoso Utomo (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2016)
Background: Indonesia medical education recruitment system recruits students directly from high school who had been influenced by mostly teacher centered learning. As part of pedagogical approach in higher education, those students will be obligatory to learn independently and effectively. Self-directed learning (SDL) is an important aspect in latest medical educational evidence which would determine students’ successfulness in learning. Self-directed learning readiness (SDLRS) is influenced by several factors including motivation, age, culture, and previous education experience. Today, the admission process in Indonesia is based on knowledge-test based only. This study aims to reveal correlation between several factors which influence students’ Self Directed Learning Readiness (SDLRS).Methods: This study used SDLRS questionnaire as a valid and reliable toll to measure the students’ self directed learning readiness and correlate with those several factors.Result: From 540 distributed questionnaires, 412 questionnaires returned back. The Spearman correlation showed significant ratio between students SDLRS score and students’ motivation. While, the analysis on age showed that age of 20 has significant ratio with students’ SDLRS score.Conclusion: among age, previous education experience, and culture; students’ internal motivation  should be considered as important factor for students’ SDLRS which will determine their successfulness in learning in medical education. These factors should be regarded as one requirement of students’ admission in medical education.